Impact of isolated exercise-Induced small airway dysfunction on exercise performance in professional male cyclists - Pigakis, K. M.; Stavrou, V. T.; Kontopodi, A. K.; Pantazopoulos, I.; Daniil, Z.; Gourgoulianis, K. (Sports, 2024)
Background: Professional cycling puts significant demands on the respiratory system. Exercise-induced bronchoconstriction (EIB) is a common problem in professional athletes. Small airways may be affected in isolation or in combination with a reduction in forced expiratory volume at the first second (FEV1). This study aimed to investigate isolated exercise-induced small airway dysfunction (SAD) in professional cyclists and assess the impact of this phenomenon on exercise capacity in this population. Materials and